2004
DOI: 10.1111/j.1439-0531.2004.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Social and Breed Effects on the Expression of a PGF2α Induced Oestrus in Beef Cows

Abstract: Social organization and breed effects following PGF2alpha were studied in mature Angus, Brahman and Senepol cows allocated into two groups (each A = 5, B = 5 and S = 5). Variables including interval to oestrus onset (IEO), oestrous duration (DE), total mounts received (TMR), and oestrous intensity (IE) were derived via HeatWatch. Breed-type influenced IEO (B = 42.6 +/- 6.7 h; S = 54.6 +/- 6.0 h; and A = 27.8 +/- 5.8 h; p < 0.003). Within breeds, dominant B (69.4 +/- 13.3 h) and S (65.5 +/- 7.4 h) cows were slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Most knowledge has relied on the many studies reporting behavioral signs in HF cows (Van Vliet and van Eerdenburg, 1996;Kerbrat and Disenhaus, 2004). Hammond (1927), Trimberger (1948), and Hurnik et al (1975) found no differences in estrous expression between breeds, but few recent studies address these questions (Cutullic et al, 2009), and several of them compare beef breeds (Rae et al, 1999;Landaeta-Hernández et al, 2004).…”
mentioning
confidence: 99%
“…Most knowledge has relied on the many studies reporting behavioral signs in HF cows (Van Vliet and van Eerdenburg, 1996;Kerbrat and Disenhaus, 2004). Hammond (1927), Trimberger (1948), and Hurnik et al (1975) found no differences in estrous expression between breeds, but few recent studies address these questions (Cutullic et al, 2009), and several of them compare beef breeds (Rae et al, 1999;Landaeta-Hernández et al, 2004).…”
mentioning
confidence: 99%
“…Behavioral signs of estrus can be observed in cattle and used for estrus detection for the purposes of artificial insemination (AI). However, these characteristics are influenced by age, milk yield, environment and hierarchy (revised in Landaeta-Hernández et al 2004). Additionally, differences can be noted among breeds (Rae et al 1999), and even among genetic groups (Bos indicus vs Bos taurus).…”
Section: Estrous Behaviormentioning
confidence: 99%
“…Conversely, several studies have reported the effect of social organization on aspects such as feed intake [12,13], weight gain [14][15][16], milk yield [17,18], and estrus expression [19].…”
Section: Introductionmentioning
confidence: 99%